Antifungal Activity of Rhizobacteria Isolated from Rice Rhizosphere Soil Against Rice Blast Fungus Pyricularia oryzae - Shyamala, L (International Journal of Pharmaceutical & Biological Archive, 2012)
Antifungal Activity of Rhizobacteria Isolated from Rice Rhizosphere Soil Against Rice Blast Fungus Pyricularia oryzae